IVFarma LLC in cooperation with Zavod Medsintez LLC extend production of biotechnological drugs for infertility treatment - article Editorial (Акушерство, гинекология и репродукция)
On November 19, 2022, the production facility manufacturing of biotechnological substances for women's reproductive health was opened at the Zavod Medsintez LLC in Novouralsk. In 2018, Zavod Medsintez LLC, together with IVFarma LLC, has launched industrial-scale operation of the first Russian follicle-stimulating hormone (FSH) drug Primapur® for infertility treatment within the framework of in vitro fertilization (IVF) protocol. Primapur® shows high efficiency, safety and quality not inferior to international analogues. The launch of the new department will substantially increase the capacity and production scale not only of Primapur®, but also other Russian medicines for reproductive health. Moreover, it is also able to provide a decent import substitution and access to world markets.